Implementasi Total Quality Management dan Innovation Capability dalam Meningkatkan Quality Performance - Devista Ayu Amalia; Dessy Insfianadewi (UNIVERSITAS PGRI MADIUN, 2020)
Total Quality Management is not the only tool to be able to advance a company to be better. Innovation is a way that can also be used as a tool to develop a company to be more developed and more innovative to improve the quality of company performance. This study aims to determine the effect of Total Quality Management and Innovation Capability on Performance Quality on pottery craftsmen in Kasongan Bantul, Yogyakarta. More competitors are entering the craft world, so the craftsmen are required to have a strategy to keep maintaining Kasongan Pottery. This study uses a quantitative approach. The research data was collected from questionnaires distributed to 135 craftsmen in Kasongan Pottery Crafts. The variables of this study were measured using statement items/questions with a 1-5 Likert Scale, starting from 1 = strongly disagree to 5 = strongly agree. The data analysis method in this research is the Structural Equation Model (SEM) using Partial Least Square (PLS) to test the hypothesis with SmartPLS 3.0 software. The results of this study indicate that Total Quality Management has a positive and significant influence on Innovation Capability. Total Quality Management and Innovation Capability has a positive and significant impact on Quality PerformanceKeywords: Total Quality Management, Innovation Capability, Quality Performance